Analysis of Bank Efficiency in Indonesia Based on Financial Ratios - Ferry Adrian (Green Publisher Indonesia, 2025)
This research aims to analyze the efficiency of banks in Indonesia based on financial ratios in the Group of Banks Based on Core Capital (KBMI) 3 and 4 for the 2021-2024 period. The Network Data Envelopment Analysis (Network DEA) approach is used to measure operational efficiency and profitability comprehensively, with an asset approach to understand the bank's resource optimization. The results of the analysis show that PT Bank Mandiri (Persero) Tbk has the highest operational efficiency, while PT Bank Permata Tbk has the lowest. In terms of profitability efficiency, PT Bank Central Asia Tbk recorded the highest value, while PT Bank Maybank Indonesia Tbk recorded the lowest. Overall, PT Bank Central Asia Tbk was the most efficient, while PT Bank Maybank Indonesia Tbk was the lowest. The panel regression model shows that the ratio of Operating Costs to Operating Income (BOPO), Capital Adequacy Ratio (CAR), and Loan to Deposit Ratio (LDR) has a significant effect on Return on Assets (ROA). This research is expected to be a reference for banks in improving efficiency and competitiveness.